Предмет: Алгебра,
автор: миленка02
Помогите решить
(2х-3)(2х+3)=4х(х+1)-1
Ответы
Автор ответа:
4
4х²-9=4х²+4х-1
-4х=8
х=-2
-4х=8
х=-2
Автор ответа:
2
(2х-3)(2х+3)=4х(х+1)-1
Раскрываем скобки:
4+6х-6х-9=4+4х-1
4-4+6х-6х-4х=9-1
-4х=8
х= -2
Ответ: -2
Раскрываем скобки:
4+6х-6х-9=4+4х-1
4-4+6х-6х-4х=9-1
-4х=8
х= -2
Ответ: -2
Похожие вопросы
Предмет: Английский язык,
автор: Ulia3108
Предмет: Русский язык,
автор: Anna4455
Предмет: Русский язык,
автор: света938
Предмет: Математика,
автор: hismatyllin1988
Предмет: Математика,
автор: Blyatvsenikizanyati